2016
DOI: 10.1371/journal.pone.0159771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Masked Replacement of Sugar-Sweetened with Sugar-Free Beverages on Body Weight Increases with Initial BMI: Secondary Analysis of Data from an 18 Month Double–Blind Trial in Children

Abstract: BackgroundSubstituting sugar-free for sugar-sweetened beverages reduces weight gain. This effect may be more pronounced in children with a high body mass index (BMI) because their sensing of kilocalories might be compromised. We investigated the impact of sugar-free versus sugary drinks separately in children with a higher and a lower initial BMI z score, and predicted caloric intakes and degree of compensation in the two groups.Methods and FindingsThis is a secondary, explorative analysis of our double-blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
(61 reference statements)
2
23
0
2
Order By: Relevance
“…However, while many intervention studies in which fructose or sugar were added to the usual daily intakes of participants documented significant increases in plasma triglycerides [29,30], few interventions involving the reduction of dietary sugar over several months or years have reported on plasma lipids. One such study, which had previously reported a lower BMI increase in children receiving ASBs than in controls receiving SSBs [31], has recently reported published data related to the study’s secondary outcomes: in spite of a two-year intervention, there was also absolutely no effect of replacing SSBs with ASBs on fasting blood triglyceride concentrations [32]. …”
Section: Discussionmentioning
confidence: 99%
“…However, while many intervention studies in which fructose or sugar were added to the usual daily intakes of participants documented significant increases in plasma triglycerides [29,30], few interventions involving the reduction of dietary sugar over several months or years have reported on plasma lipids. One such study, which had previously reported a lower BMI increase in children receiving ASBs than in controls receiving SSBs [31], has recently reported published data related to the study’s secondary outcomes: in spite of a two-year intervention, there was also absolutely no effect of replacing SSBs with ASBs on fasting blood triglyceride concentrations [32]. …”
Section: Discussionmentioning
confidence: 99%
“…of growth and energetic balance to estimate the degree of caloric compensation that each child had to compensate for the loss of the sugar calories from their drinks by increasing their intake of kilocalories from other foods and beverages. Children with overweight (16%) and obesity (3%) also participate in the trial (Katan et al, 2016). Ot was possible to verify that the children with BMO above the media had a reduction of the tendency to compensate the changes in the intake of calories.…”
Section: Efsa and Us Fdamentioning
confidence: 99%
“…Data Riskesdas tahun 2010 menunjukkan bahwa prevalensi nasional kegemukan pada remaja usia 13-15 tahun sebesar 2,5% (5). Provinsi Banten merupakan salah satu dari 14 provinsi yang memiliki prevalensi kegemukan pada remaja usia 13 Hasil analisis regresi logistik permodelan digunakan untuk mengetahui adanya hubungan variabel pendidikan ibu, pekerjaan ibu, pendidikan ayah, pekerjaan ayah dan asupan gula sederhana dengan kejadian obesitas. Hasil analisis model 1 menunjukkan bahwa pendidikan ibu, pekerjaan ibu, pendidikan ayah, dan asupan gula sederhana memiliki hubungan yang signifikan secara statistik terhadap kejadian obesitas (p<0,05), sedangkan pekerjaan ayah tidak memiliki hubungan yang signifikan terhadap kejadian obesitas.…”
Section: Pendahuluanunclassified
“…Sebuah penelitian pada tahun 2016 menjelaskan bahwa terdapat hubungan yang signifikan antara konsumsi minuman manis dengan Indeks Massa Tubuh (IMT) pada anak-anak (13). Konsumsi minuman bebas gula selama 18 bulan mengurangi skor IMT sebesar 0,05 SD pada kelompok dengan IMT yang lebih rendah dan sebesar 0,21 SD pada kelompok dengan IMT yang lebih tinggi.…”
Section: Pembahasanunclassified